Representações literárias dos "anos de chumbo" em Batismo de sangue e Você vai voltar pra mim - Rocha, Fernanda Reis da (2019)
Among the innumerable artistic manifestations aimed at resuming and debating the Brazilian dictatorship (1964-1985) - an anti-democratic, oppressive and arbitrary government in which many men and women suffered directly and indirectly the experimentation of extreme situations (torture, secrecy,imprisonment and exile), and irretrievable measures (forced disappearance and political murder) -, this thesis selected the narratives Batismo de Sangue (1982), written by Frei Betto, and the collection Você vai voltar pra mim e outros contos (2014), assembled by Bernardo Kucinski, as a scope of examination. Aiming at analyzing the three dimensions assumed by the body (identity component, instituting component and violence experiencing agent) in the midst of the military regime, this work was based firstly on the reading and interpretation of the two fiction work and, in the second moment, on theoretical studies by Michael Foucault, Hanna Arendt, Beatriz Sarlo, Elio Gaspari, Marcelo Ridenti, Antonio Cândido, Euridice Figueiredo, Maria Rita Kehl as well as on official documents such as those elaborated by the Archdiocese of São Paulo and the Political Deaths and Disappearances Special Committee. Although belonging to different genres of literature and distant periods of time, these writing work cover the same theme, "the years of lead" in Brazil, and the authors turned the period itself into fiction, as well as its immediate and subsequent consequences. In order to do so, they have assumed sometimes a more lyrical and metaphorical literary approach, and sometimes an inclination towards more rough and realistic descriptions and demonstrations, trying to bring to surface the different and diverse visions and versions of the same story